2010
DOI: 10.1016/j.canlet.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and estradiol are equipotent in antagonizing cisplatin-induced cytotoxicity in breast cancer cells

Abstract: Resistance to chemotherapy is a major problem facing breast cancer patients. Cisplatin, a highly effective DNA-damaging drug, has shown only little success in breast cancer treatment. We are reporting that low nanomolar doses of bisphenol A (BPA) or estradiol antagonize cisplatin cytotoxicity in breast cancer cells, with their effects not mediated via classical estrogen receptors. Although both compounds increase the expression of Bcl-2, a Bcl-2 inhibitor completely blocked the protective effects of BPA while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…Since incurable cancer, which afflicts over 450 persons per 100,000 annually, is a growing health epidemic, it is important to establish a relationship between environmental xenogens (i.e., endocrine disruptors) and cancer (30). Indeed, recent studies on this subject indicate a growing correlation between high exposure to endocrine disruptors (e.g., bisphenol A, xenoestrogens, polycyclic aromatic hydrocarbons) and cancer risk or drug response (13,(31)(32)(33)(34)(35)(36)(37). The question is particularly relevant given that recent developments in cancer drug therapy (e.g., targeted therapy) are markedly improving survivability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since incurable cancer, which afflicts over 450 persons per 100,000 annually, is a growing health epidemic, it is important to establish a relationship between environmental xenogens (i.e., endocrine disruptors) and cancer (30). Indeed, recent studies on this subject indicate a growing correlation between high exposure to endocrine disruptors (e.g., bisphenol A, xenoestrogens, polycyclic aromatic hydrocarbons) and cancer risk or drug response (13,(31)(32)(33)(34)(35)(36)(37). The question is particularly relevant given that recent developments in cancer drug therapy (e.g., targeted therapy) are markedly improving survivability.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, over the last several decades, our burden of environmental xenotoxins has increased substantially. Recent work implicates several xenogens in cancer cell growth and drug resistance (13,(31)(32)(33)(34)(35)(36)(37). Indeed, the molecular pathways governing the tissue-specific phenotypes mediated by chronic exposure to endocrine disruptors are varied, and it is clear that some important effects are mediated via nuclear receptors.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested us that cinobufacini could enhance killing effect of osteosarcoma cells when combined with cisplatin, therefore, a greater anti-tumor effect would be triggered if cinabufotalin were used in the chemotherapy. Since there were a great number reports about side effects on digestive, nervous, blood and other body systems due to application of cisplatin during the regular chemotherapy of osteosarcoma patients (Konstantakou et al, 2009;LaPensee et al, 2010;Maroto et al, 2011;Rotte et al, 2010;Sprowl et al, 2012), we suppose ,combination of cinobufacini and cisplatin will avoid all these side effects of chemotherapy, and by this way, cinobufacini will promote from the second-line to the first-line anti-tumor drugs and will play a more important role in osteosarcoma therapy. In addition, our research showed the killing effect by the application of cinobufotalin and cisplatin were fulfilled by inducing apoptosis of osteosarcoma cells which were revealed from the cell morphology (Figure2A-2D), cell apoptosis (Figure2E -2H) and FCM analysis (Figure3A-3B).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that BPA is associated with reproductive disorders, cardiovascular diseases, abnormal liver function, and diabetes in human beings (Lang et al, 2008;vom Saal and Myers, 2008;Soto and Sonnenschein, 2010). Furthermore, many studies have shown that BPA influences the promotion or progression of many cancers such as seminoma, prostate cancer, and breast cancer (Bouskine et al, 2009;Hess-Wilson, 2009;LaPensee et al, 2010). In particular, children are vulnerable to EE exposure because they have a relatively large body surface area and limited catabolism (Mello-da-Silva and Fruchtengarten, 2005).…”
Section: Introductionmentioning
confidence: 99%